Preservation of graft function in low-risk living kidney transplant recipients treated with a combination of sirolimus and cyclosporine - Machado,P.G.P. (2004)
The use of sirolimus (SRL) in combination with full doses of cyclosporin A (CsA) results in reduced one-year kidney allograft function, which is associated with shorter long-term allograft survival. We determined the effect of reduced CsA exposure on graft function in patients receiving SRL and prednisone. Ninety recipients of living kidney transplants receiving SRL (2 mg/day, po) were compared to 35 recipients receiving azathioprine (AZA, 2 mg kg-1 day-1, po). All patients also received CsA (8-10 mg kg-1 day-1, po) and prednisone (0.5 mg kg-1 day-1). Efficacy end-point was a composite of biopsy-confirmed acute rejection, graft loss, or death at one year. Graft function was measured by creatinine, creatinine clearance, and graft function deterioration between 3 and 12 months (delta1/Cr). CsA concentrations in patients receiving SRL were 26% lower. No differences in one-year composite efficacy end-point were observed comparing SRL and AZA groups (18 vs 20%) or in the incidence of biopsy-proven acute rejection (14.4 and 14.3%). There were no differences in mean ± SD creatinine (1.65 ± 0.46 vs 1.60 ± 0.43 mg/dl, P = 0.48) or calculated creatinine clearances (61 ± 15 vs 62 ± 13 ml/min, P = 0.58) at one year. Mean ± SD delta1/Cr (-11 ± 17 vs -14 ± 15%, P = 0.7) or the percentage of patients with >20% (26 vs 31%, P = 0.6) or >30% delta1/Cr (19 vs 17%, P = 1) did not differ between the two groups. The use of 2-mg fixed oral doses of SRL and reduced CsA exposure was effective in preventing acute rejection and preserving allograft function.